Trends in Upper Gastrointestinal Bleeding in Children: The Impact of Helicobacter pylori Infection and Non-Steroidal Anti-Inflammatory Drug Use - Felicia Galos; Mara Ioana Ionescu; Mihai Daniel Luca Mirea; Anca Andreea Boboc; Andreea Ioan; Catalin Boboc (MDPI AG, 2024)
Upper gastrointestinal bleeding (UGIB) is a significant concern in children, contributing to 6-20% of cases in pediatric intensive care units. This study evaluates the roles of Helicobacter pylori (H. pylori) infection and non-steroidal anti-inflammatory drug (NSAID) usage in the etiology of UGIB in children, with a particular focus on trends observed during the COVID-19 pandemic. We conducted a retrospective analysis of 103 pediatric patients who underwent esophagogastroduodenoscopy (EGD) for UGIB between January 2015 and December 2023. Of these, 88 patients were included in the final analysis, where the source of bleeding was successfully identified. Hematemesis was the most common presentation, and the source of bleeding was identified in 85.43% of cases. The prevalence of H. pylori infection remained stable across the pre-pandemic (39.7%) and post-pandemic (36.7%) periods. However, NSAID usage increased nearly threefold during the pandemic, with 36.7% of post-pandemic UGIB cases associated with NSAID use, compared to 12.1% pre-pandemic. These findings underscore the significant roles of H. pylori and NSAID use in pediatric UGIB, with a notable increase in NSAID-related cases during the pandemic.